Reconstruction of Business Licensing Governance Through Online Single Submission (OSS) from the Perspective of Efficiency and Legal Certainty: Rekonstruksi Tata Kelola Perizinan Usaha Melalui Online Single Submission (OSS) Menurut Perspektif Efisiensi dan Kepastian Hukum - Leonardi, Leonardi; Tundjung, Tundjung (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Indonesia has introduced the Online Single Submission (OSS) system to streamline licensing and strengthen legal certainty in business administration. Specific Background: Despite continuous regulatory reforms, OSS implementation still encounters technical, institutional, and regulatory inconsistencies between central and regional authorities. Knowledge Gap: Existing studies rarely integrate analyses of procedural efficiency and legal certainty while also proposing a structured governance reconstruction model. Aims: This study examines OSS performance through the lenses of efficiency and legal certainty and formulates a comprehensive reconstruction framework for improved licensing governance. Results: Findings show that OSS effectively simplifies several procedures but remains hindered by uneven digital infrastructure, inconsistent regulatory synchronization, limited institutional readiness, and the absence of an internal dispute-resolution mechanism. Novelty: The study offers an integrated reconstruction model combining legal harmonization, institutional coordination, and technological strengthening to address both efficiency and legal certainty deficits. Implications: Strengthening OSS governance is essential for enhancing investment climate, ensuring predictable licensing outcomes, and supporting good governance principles in Indonesia’s public administration. Highlights: Highlights the dual challenges of efficiency gaps and legal uncertainty in OSS implementation. Emphasizes the need for regulatory harmonization and institutional coordination across sectors and regions. Proposes a comprehensive reconstruction model integrating legal, institutional, and technological improvements. Keywords: Online Single Submission, Business Licensing, Efficiency, Legal Certainty, Governance Reconstruction